2021
DOI: 10.3390/molecules26237247
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Solvated DMABN: Excited State Quantum Dynamics and Dual Fluorescence Spectra

Abstract: In this work, we report a complete analysis by theoretical and spectroscopic methods of the short-time behaviour of 4-(dimethylamino)benzonitrile (DMABN) in the gas phase as well as in cyclohexane, tetrahydrofuran, acetonitrile, and water solution, after excitation to the La state. The spectroscopic properties of DMABN were investigated experimentally using UV absorption and fluorescence emission spectroscopy. The computational study was developed at different electronic structure levels and using the Polarisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…The structures thus cover the configurations needed to fit with the known behaviour of these molecules in the first 100 fs after photo-activation as the torsional motion is strongly activated in ethene 24 and fulvene, 31 while DMABN remains planar. 33 The similarity between the LVC and direct dynamics results for IC2 and IC3 indicate that the potential surfaces are well characterised by the single conical intersection seam of the LVC model. The main addition from the direct dynamics is allowing the molecules to move away from the intersection faster, leading to reduced population transfer due to new pathways being available in the active states.…”
Section: Direct Dynamicsmentioning
confidence: 72%
See 2 more Smart Citations
“…The structures thus cover the configurations needed to fit with the known behaviour of these molecules in the first 100 fs after photo-activation as the torsional motion is strongly activated in ethene 24 and fulvene, 31 while DMABN remains planar. 33 The similarity between the LVC and direct dynamics results for IC2 and IC3 indicate that the potential surfaces are well characterised by the single conical intersection seam of the LVC model. The main addition from the direct dynamics is allowing the molecules to move away from the intersection faster, leading to reduced population transfer due to new pathways being available in the active states.…”
Section: Direct Dynamicsmentioning
confidence: 72%
“…The structures thus cover the configurations needed to fit with the known behaviour of these molecules in the first 100 fs after photo-activation as the torsional motion is strongly activated in ethene 24 and fulvene, 31 while DMABN remains planar. 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of dual fluorescence in 4-(dimethyl­amino)­benzonitrile (DMABN, Figure ), the valence excited electronic states of DMABN and their evolution following photoexcitation have been studied extensively to gain a mechanistic understanding of this phenomenon. Initially the state reversal model was proposed to explain the dual fluorescence . In the context of this model, it was suggested that initial excitation to the lowest absorption band leads to population of S 1 and S 2 states.…”
Section: Introductionmentioning
confidence: 99%
“…1), 1 the valence excited electronic states of DMABN and their evolution following photoexcitation have been studied extensively to gain mechanistic understanding of this phenomenon. [2][3][4][5][6][7][8][9] Initially the state reversal model was proposed to explain the dual fluorescence. 10 In the context of this model, it was suggested that initial excitation to the lowest absorption band leads to population of S 1 and S 2 states.…”
Section: Introductionmentioning
confidence: 99%